The Influence of Teaching methods of Khawaja Yusuf Hamadānī on the Formation of Sufi Orders in Central Asia - Mansurov, Fatkhiddin (The Canada International Conference on Education, 2016)
This study investigates the teachings and influence of Khawaja Yusuf Hamadānī who is a prominent Sufi of the 11-12th centuries on the subsequent formation of Sufi orders in Central Asia. The study mainly has three objectives that are firstly, to describe Hamadānī’s life; secondly, to explore his teachings and finally, to highlight the role and influence of Yusuf Hamadānī in Sufism. As a dedicated work on the subject, the study is considered as one of the significant research works conducted on Sufism periods in Central Asia, since new information and conclusions have been proposed to the existing literature as a result of consideration on Hamadānī’s life and influence. He has become one of the Sufi Masters with the most number of disciples and educated Sufi leaders such as Khawaja Abdulkhāliq Ghijduwānī and Khawaja Ahmad Yasawī who were the founders of important Sufi orders which are known as Khawajagan-Naqshbandiyya and Yasawiyya. Therefore, they have a significant role in bringing Sufism up to the present days.